Changes in the Vector of Industrial Policy and Possibilities for Innovative Development of the Industrial Regions - Romanova, Olga Aleksandrovna; Starikov, Yevgeny Nikolayevich (Economy of Regions, 2015)
In the present paper, reasons for the increased interest in industrial policy, both in developed and developing countries are explained. The systematization of the development results of the Russian industry from 1989 to 2014 showed a lack of systematic selection of its priorities, preventing the formation of a strategic vector of industrial policy. The desired industrial policy diversity is established at the different economic development stages of the country. In the context of economic sanctions against Russia, it is shown that the emergence of a new industrial policy vector is connected to the need for import substitution and concomitant changes in the development model of the domestic economy. The dynamics and characteristics of the industrial development area are shown by the example of a highly developed region like the Central Urals. The total level of innovation activity of organizations continues to be low and composes only 12 %, although in the manufacturing sector this index is higher than the regional economy index by four absolute percentage points. The industrial policy of the Middle Urals is analyzed, and innovation drivers of the industrial sector of the regional economy are established. The possibilities of the defense, civil engineering, mining, chemical and pharmaceutical, and forest complexes of Sverdlovsk Region to implement the import substitution policy are revealed. The most significant investment projects that will reduce the import dependence of the regional economy are presented. The possibilities of the research sector and created innovation infrastructure of the region in solving this problem are shown. The necessity of the regional laws on industrial policy elaboration, developing the basic regulations of the Federal Law "On Industrial Policy in the Russian Federation" in proved.